Impact of laparoscopic surgeries on optic nerve sheath diameter (ONSD) in children - Mohsina Yasmeen; Sumaiya Sabreen; Akshay Bettanayaka; Saraswathi Nagappa (Saudi Journal of Anaesthesia)
Background: The pneumoperitoneum in laparoscopic surgeries elevates intracranial ICP because of the increased abdominal pressure, and ICP increases even further in the Trendelenburg position. A new noninvasive method to measure optic nerve sheath diameter (ONSD) via ultrasonography detects the raised ICP is reliable and inexpensive and can be repeated many times. Methods: In this prospective observational study, 23 pediatric patients aged between 5 and 16 years, undergoing elective laparoscopic procedures under general anesthesia, were included. After endotracheal intubation with proper aseptic precautions, ocular ultrasound was performed to measure baseline ONSD in both eyes. Later, pneumoperitoneum was established by maintaining the intra-abdominal pressure (IAP) at 12 cmH2O. Again, ONSD was estimated at 15 minutes of pneumoperitoneum and observed for any variation from the previous readings. The cutoff considered for ONSD was 5 mm, above which the intracranial pressure (ICP) was regarded as increased. Results: In our study, the mean age of subjects was 9.67 ± 5.18 years. The majority were males (60.9%). The subjects showed an increase in ONSD at the 15th minute after inducing pneumoperitoneum using abdominal CO2 insufflation, in comparison with the baseline values, in the left eye [4.67 ± 0.48, P 0.016] and the right eye [4.63 ± 0.43]. The readings of ONSD were observed to be <5 mm, not statistically significant. Conclusion: USG-guided ONSD measurements serve as a valuable tool in ensuring optimal intra-abdominal pressures and safe administration of anesthesia for patients undergoing laparoscopic surgery, particularly those vulnerable to an increase in ICP.